Carbon ion radiotherapy for locally advanced squamous cell carcinoma of the external auditory canal and middle ear. Issue 4 (26th May 2015) - Koto, Masashi; Hasegawa, Azusa; Takagi, Ryo; Sasahara, Go; Ikawa, Hiroaki; Mizoe, Jun‐etsu; Jingu, Keiichi; Tsujii, Hirohiko; Kamada, Tadashi; Okamoto, Yoshitaka; ,
Abstract: Background: The prognosis of advanced squamous cell carcinoma (SCC) of the external auditory canal and middle ear remains poor. Carbon ion radiotherapy (C‐ion RT) has shown promise for locally advanced head and neck cancer. Therefore, we evaluated the safety and efficacy of C‐ion RT for locally advanced SCC of the external auditory canal and middle ear. Methods: The cases of 13 patients with advanced (T3 and T4) SCC of the external auditory canal and middle ear who received C‐ion RT as the primary treatment were reviewed. Results: The median follow‐up for all patients and the 7 surviving patients was 12 and 32 months, respectively. The 1‐year and 3‐year local control and overall survival (OS) rates were 72% and 54% and 70% and 40%, respectively. Severe temporal bone necrosis was observed in 2 patients. Conclusion: C‐ion RT is effective and generally safe for locally advanced SCC of the external auditory canal and middle ear. © 2015 Wiley Periodicals, Inc. Head Neck 38: 512–516, 2016